The Extent of Ethical Leadership Among Youth in Malaysia - Abd Rahim, Nazahah; Ahmad Zaluki, Nurwati Ashikkin (2018)
Ethical leadership is a form of leadership where individuals demonstrate acceptable and appropriate conducts in every aspect of their life. However, in Malaysia this form of leadership seems to be lacking as one of the biggest corporate scandals in history has been linked to its former Prime Minister. This paper presents an exploratory study assessing the extent of ethical leadership among youth in Malaysia. Since youth represents one of the most valuable assets in the development of a nation, it is important to understand the traits of these future leaders. Quantitative method was employed and data were collected through questionnaires involving 600 university students from three different universities in Malaysia. The questionnaire was adopted from Ethical Leadership at Work (ELW) instrument containing seven ethical leadership traits. The findings revealed that “integrity” scored the highest mean score while “fairness” scored the lowest. However, with a narrow range between the mean scores, the study also concludes that Malaysian youth embraced various ethical leadership traits and have acceptable level of ethical leadership. Since there are limited studies examining ethical leadership among youth, this study is among the first to explore this issue especially in a developing country such as Malaysia